2016
DOI: 10.1080/17451000.2015.1112016
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcoding for assessment of exotic molluscs associated with maritime ports in northern Iberia

Abstract: Ports are gateways for aquatic invasions. New arrivals from maritime traffic and disturbed environmental conditions can promote the settlement of exotic species. Molluscs fall into the most prevalent group of invasive species and can have a tremendous impact on aquatic ecosystems. Here we have investigated exotic molluscs in three ports with different intensities of maritime traffic in the Cantabrian Sea. DNA barcodes were employed to identify the species using BLASTn and BOLD IDS assignment. Deep morphologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 30 publications
2
32
1
Order By: Relevance
“…This is the first documented record of O. equestris in Hawaiian waters. The O. stentina/aupouria/equestris species complex is globally distributed, found along Atlantic coasts, the Mediterranean, North Africa, New Zealand, Japan, China, and South America (Crocetta et al 2013; Hamaguchi et al 2017; Hu et al 2019; Lapègue et al 2006; Pejovic et al 2016). At this time, it is uncertain whether O. equestris in Hawai’i is native or introduced, though it seems likely to be native given the wide distribution of O. equestris in both the Atlantic and Pacific oceans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first documented record of O. equestris in Hawaiian waters. The O. stentina/aupouria/equestris species complex is globally distributed, found along Atlantic coasts, the Mediterranean, North Africa, New Zealand, Japan, China, and South America (Crocetta et al 2013; Hamaguchi et al 2017; Hu et al 2019; Lapègue et al 2006; Pejovic et al 2016). At this time, it is uncertain whether O. equestris in Hawai’i is native or introduced, though it seems likely to be native given the wide distribution of O. equestris in both the Atlantic and Pacific oceans.…”
Section: Discussionmentioning
confidence: 99%
“…The selected models were HKY+I+G and HKY+G respectively for 16S and COI . We constructed Bayesian trees via MrBayes implemented in Geneious, using the following species for comparison: C. gigas (DQ839414, FJ743509, AY632550, JF808180, JF700177 (Pie et al 2006; Sayers et al 2018; Wang et al 2004; Zhang et al 2013)), C. gigas angulata (KC170323, KC170322 (Peng-yun 2013; Sayers et al 2018)), D. sandvichensis (KC847121, EU815985 (Sayers et al 2018)), O. angasi (AF052063 (Jozefowicz & Foighil 1998; Sayers et al 2018)), O. angelica (KT317127, KT317140, KT317449 (Raith et al 2015; Sayers et al 2018)) , O. chilensis (AF052065 (Jozefowicz & Foighil 1998; Sayers et al 2018)), O. circumpicta (MG560202 (Sayers et al 2018), O. conchaphila (KT317173, FJ768528, KT317494 (Polson et al 2009; Raith et al 2015; Sayers et al 2018)), O. denselamellosa (FJ743511, HQ660995, KP067907 (Kim et al 2015; Liu et al 2011; Sayers et al 2018)), O. edulis (JQ611449, AF540595, KJ818235 (Malkowsky & Klussmann-Kolb 2012; Morton et al 2003; Pejovic et al 2016; Sayers et al 2018)), O. futamiensis (LC051603 (Hamaguchi et al 2017; Sayers et al 2018)), O. lurida (FJ768559, FJ768554, KT317504 (Polson et al 2009; Raith et al 2015; Sayers et al 2018)), O. permollis (AY376605, AY376606, DQ226526 (Kirkendale et al 2004; Sayers et al 2018)) , O. puelchana (AF052073, DQ226521 (Jozefowicz & Foighil 1998; Sayers et al 2018)), and O. stentina/aupouria/equestris species complex (Table 3). For outgroups, we used sequences from Hyotissa imbricata (KC847136 and AB076917 (Matsumoto 2003; Sayers et al 2018)).…”
Section: Methodsmentioning
confidence: 99%
“…Scale bar indicates five substitutions per 100 site alien species remains unanswered. This species is widely distributed along Atlantic, Mediterranean, North African, New Zealand and South American coasts (Lapègue et al 2006;Gofas et al 2011;Crocetta et al 2013a, b;Pejovic et al 2016). In several cases, supposedly distinct Ostrea species in separate geographical areas have been revised to a single species by molecular analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Polson et al (2009) compared the species using molecular markers and post-hoc morphological characteristics and concluded that O. lurida and O. conchaphila were separate species. In this manner, DNA markers and molecular biological methods have been used to resolve taxonomic problems caused by species identification of flat oysters based on morphological features alone (O'Foighil et al 1999;Jozefowicz and O'Foighil 1998;Hurwood et al 2005;Lapègue et al 2006;Lazoski et al 2011;Pejovic et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Biosecurity, particularly in regards to the identification of specimens in quarantine situations, has benefited greatly from the use of DNA sequencing approaches to identify known pests Ball 2005, Ball andArmstrong 2006) and exotic species (Pejovic et al 2016, Ardura andPlanes 2017), and in some locations national, and even international, programs are being established to integrate DNA sequencing and biosecurity efforts (e.g., Hodgetts et al 2016). Yet, DNA approaches fail to identify potential quarantine species when previously sequenced individuals of that species are missing from the reference library.…”
Section: Applicability For Biosecurity and Quarantine Monitoringmentioning
confidence: 99%